Eudesmane and aromadendrane sesquiterpenoids from the Vietnamese soft coral Sinularia erecta. Issue 15 (3rd August 2018) - Huong, Nguyen Thi; Ngoc, Ninh Thi; Thanh, Nguyen Van; Dang, Nguyen Hai; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Thung, Do Cong; The, Ho Van; Tuan, Vo Sy; Kiem, Phan Van; Minh, Chau Van
Abstract: Using various chromatographic separations, eight sesquiterpenoids (1 –8 ), including one new compound 3 β, 5 α -dihydroxyeudesma-4(15), 11-diene (1 ), were isolated from the MeOH extract of the Vietnamese soft coral Sinularia erecta . The structure elucidation was confirmed by spectroscopic experiments including 1D and 2D NMR and HR-ESI-MS. The cytotoxic activities against three human cancer cell lines (A-549, HeLa and PANC-1) of all isolated compounds were evaluated by MTT-based colorimetric assays. Compound1 exhibited selective cytotoxicity against the A549 cell line with IC50 of 14.79 ± 0.91 μM. Abstract :